Adapting Mother Tongue-Based Instructional Models to Address Gender Disparities in Literacy and Numeracy Skills - Laksana, Dek Ngurah Laba; Qondias, Dimas; Veliz, Leonardo; Chiu, Chunta; Utami, Ketut Herya Darma; Listyana, I Gusti Agung Ayu Putu (International Journal of Language Education, 2025)
Gender disparities in literacy and numeracy continue to challenge equitable education, especially in linguistically diverse and indigenous communities. In East Nusa Tenggara, Indonesia, the integration of mother tongue-based instructional models offers a promising approach to address these inequities. While the benefits of mother tongue education on overall academic achievement are well documented, its specific role in mitigating gender gaps remains insufficiently examined. This study aim to analyze mother tongue-based multilingual education (MTB-MLE) can be adapted to support gender-equitable learning outcomes in literacy and numeracy among elementary students. The method employed a mixed-method approach. The quantitative component involved quasi-experimental research, meanwhile the qualitative aspect included interviews. Research participants included early-grade elementary students in the Riung ethnic region, comprising a total sample of 168 students (70 male and 98 female). The quantitative data were analyzed using ANCOVA to evaluate differences in pretest and post-test results based on gender, while qualitative data underwent thematic analysis to identify facilitating factors and barriers in implementing the instructional model. Findings reveal that both male and female students benefited significantly from mother tongue-based instruction. Notably, female students showed greater improvements in literacy, while male students demonstrated slightly higher gains in numeracy. These results underscore the potential of culturally responsive, language-based instructional models to promote inclusive and equitable education. By situating learning within students’ linguistic and cultural contexts, mother tongue-based instruction not only enhances academic performance but also supports gender-sensitive pedagogy and curriculum development. This study contributes to the global discourse on language education by offering insights into how localized pedagogical strategies can be leveraged to address gender disparities.